The Effect of E-Service Quality, E-Trust, and Ease of use on E-Satisfaction on the JKN Mobile Application : Study on JKN Mobile Application Users in Kolaka Regency - Sahra Amanda Putri; Andry Stepahnie Titing; Muhammad Stiadi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the influence of E-Service Quality, E-Trust, and Ease of Use on E-Satisfaction among users of the Mobile JKN application in Kolaka Regency. Employing a quantitative method, data were collected through structured questionnaires distributed to 150 purposively selected respondents. The analysis was conducted using Structural Equation Modeling with the Partial Least Squares (PLS-SEM) technique via SmartPLS 4.0. The results reveal that all three independent variables significantly affect E-Satisfaction, with Ease of Use having the most substantial influence, followed by E-Service Quality and E-Trust. The measurement model demonstrates strong reliability and validity through AVE, composite reliability, and Cronbach’s Alpha values that meet recommended thresholds. The structural model explains 54% of the variance in E-Satisfaction, indicating a moderate predictive capability. These findings emphasize the importance of usability, trust, and digital service performance in enhancing user satisfaction with public health service applications. The study provides practical implications for developers and policymakers in improving the functionality and trustworthiness of digital platforms, particularly in the public health sector.